Development and Utilization of Domino Card Media in Thematic Learning of Mathematics for Elementary School Students - Asiya, Siti; Umam, Khotibul; Suhardi, Andi; Arpilleda, Alcher J. (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Learning media can facilitate students' and educators' teaching and learning processes by increasing students' learning motivation. Learning media attract students' attention and act as a conduit for messages between educators and students. They make the material easier to understand and prevent boredom. This study aims to 1) Produce Domino Card learning media for Mathematics for class II at Madrasah As-Syafi'iyah Kencong Jember, 2) Determine the feasibility of the Domino Card learning media, and 3) Assess the effectiveness of the Domino Card learning media. The study used the Research and Development (R&D) method and the ADDIE model, which involved ten students from class II at Leces Islamic Elementary School. The final product, Modified Domino Card media, was validated by media, material, and learning experts, resulting in a validity score of 93%, categorizing it as very valid. The N-Gain Score calculation showed an average learning outcome increase of 83%, indicating the media's effectiveness. Thus, domino card learning media is valid and effective in improving the thematic learning of mathematics content in class II of Madrasah As-Syafi'iyah Kencong Jember. Innovative learning media such as Domino Cards can increase student motivation and engagement in the learning process, thus helping students better understand the material more interestingly and interactively.